Removal of Dibenzofuran from aqueous solution by sugarcane bagasse-based biochar - Minh Nhut Nguyen; Ba Huy Tran; Khoi Nghia Nguyen; Huynh Giao Dang (CTU Journal of Innovation and Sustainable Development)
Dibenzofuran (DBF) has been considered an environmental risk due to its high toxicity and risks to human health and ecosystems. Among wastewater treatment technologies, the adsorption process has emerged as a potential solution to remove organic pollutants efficiently, including dibenzofuran, in wastewater. The study aims to investigate the feasibility of sugarcane bagasse-based biochar for DBF removal through adsorption. Biochar characteristics showed a high specific surface area of up to 498.97 m2/g and abundant functional groups on the material surface, resulting in high removal performance of DBF with average adsorption efficiency and adsorption capacity reaching maximum values of 98.43% and 96.77 mg/g, respectively. The optimum parameters were suggested for DBF removal: pyrolysis temperature of 700oC, contact time of 50 min, biochar dosage of 0.5 g/L, and DBF concentration of 40 mg/L. Furthermore, the results of adsorption kinetics and adsorption isotherms indicated that the adsorption process benefits DBF removal. Pseudo-second-order model and Langmuir model can describe the DBF removal process due to the best fit to experimental data (R2 > 0.98). Based on these findings, sugarcane bagasse-based biochar could be utilized efficiently to remove DBF from wastewater.